Inter-ethnic friendship and hostility between Roma and non-Roma students in Hungary: The role of exposure and academic achievement - Tamás Hajdu; Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2017)
This study examines friendship and hostility relations between Roma students and the ethnically homogeneous non-Roma majority in Hungarian schools. Using data on friendship and hostility relations of 15-year-old students from 82 schools the study focuses on the interaction between exposure to the other ethnic group and academic achievement of Roma students. High-achieving Roma students are shown to have significantly more friends and fewer adversaries than low-achieving ones, due to better inter-ethnic relations while having similar within-ethnic group relations. As a result, higher exposure to Roma students translates to more friendship and less hostility from non-Roma students in environments where more of the Roma students have higher achievement. Therefore, policies helping the achievement of Roma students can have immediate as well as long-term positive effects. Simulations suggest that a mixed policy of desegregation and closing the achievement gap may best foster positive interethnic relations. The results also support that exposure is more likely to improve intergroup contact if status is more equal.
Keywords: J15; I24; 330; Social interactions; Minority students; Achievement gap